Application of the optimizing health literacy and access (Ophelia) process in partnership with a refugee community in Australia: Study protocol - Jawahar, Zaman; Elmer, Shandell; Hawkins, Melanie; Osborne, Richard H. (Frontiers in Public Health, 2023)
Refugees experience health inequities resulting from multiple barriers and difficulties in accessing and engaging with services. A health literacy development approach can be used to understand health literacy strengths, needs, and preferences to build equitable access to services and information. This protocol details an adaptation of the Ophelia (Optimizing Health Literacy and Access) process to ensure authentic engagement of all stakeholders to generate culturally appropriate, needed, wanted and implementable multisectoral solutions among a former refugee community in Melbourne, Australia. The Health Literacy Questionnaire (HLQ), widely applied around the world in different population groups, including refugees, is usually the quantitative needs assessment tool of the Ophelia process. This protocol outlines an approach tailored to the context, literacy, and health literacy needs of former refugees. This project will engage a refugee settlement agency and a former refugee community (Karen people origin from Myanmar also formerly knowns as Burma) in codesign from inception. A needs assessment will identify health literacy strengths, needs, and preferences, basic demographic data and service engagement of the Karen community. This community will be engaged and interviewed using a semi-structured interview based on the Conversational Health Literacy and Assessment Tool (CHAT) will cover supportive professional and personal relationships, health behaviors, access to health information, use of health services, and health promotion barriers and support. Using the needs assessment data, vignettes portraying typical individuals from this community will be developed. Stakeholders will be invited to participate in ideas generation and prioritization workshops for in-depth discussion on what works well and not well for the community. Contextually and culturally appropriate and meaningful action ideas will be co-designed to respond to identified health literacy strengths, needs, and preferences of the community. This protocol will develop and test new and improved methods that are likely to be useful for community-based organizations and health services to systematically understand and improve communication, services and outcomes among disadvantaged groups, particularly migrants and refugees.